Social Enterprise, Population Health and Sustainable Development Goal 3: A Public Health Viewpoint - Gloria Macassa (Ubiquity Press, 2021)
Although there is no consensus on the definition of "social enterprises (SEs)," various scholars have agreed that SEs are "sustainable ventures that combine business principles with a passion for social impact." Using a public health lens, this viewpoint paper attempts to discuss the potential role SEs might play in the achievement of sustainable population health and Sustainable Development Goal 3 (SDG 3): "Health for all at all ages." Through their impact on social determinants of health (the conditions in which people are born, grow, work, and age), SEs have a potential to contribute to SDGs, specifically SDG 3. They can do so by acting on and modifying the economic, social and environmental challenges communities face, to help promote health and wellbeing and improve the quality of life among children, adolescents, working adults and elderly across countries, societies and generations. Social enterprises present an opportunity to engage business as partners in health promotion - which is yet to materialize in all societies globally.